ZmBET5L1 inhibits primary root growth and decreases osmotic stress tolerance by mediating vesicle aggregation and tethering in maize. (25th December 2022) - Zhao, Ran; Li, Nan; Lin, Qianrun; Li, Manfei; Shen, Xiaomeng; Peng, Yong; Du, Yanfang; Ning, Qiang; Li, Yunfu; Zhan, Jimin; Yang, Fang; Xu, Fang; et al.
Abstract: Improving osmotic stress tolerance is critical to help crops to thrive and maintain high yields in adverse environments. Here, we characterized a core subunit of the transport protein particle (TRAPP) complex, ZmBET5L1, in maize using knowledge‐driven data mining and genome editing. We found that ZmBET5L1 can interact with TRAPP I complex subunits and act as a tethering factor to mediate vesicle aggregation and targeting from the endoplasmic reticulum to the Golgi apparatus. ZmBET5L1 knock‐out increased the primary root elongation rate under 20% polyethylene glycol‐simulated osmotic stress and the survival rate under drought stress compared to wild‐type seedlings. In addition, we found that ZmBET5L1 moderates PIN1 polar localization and auxin flow to maintain normal root growth. ZmBET5L1 knock‐out optimized auxin flow to the lateral side of the root and promoted its growth to generate a robust root, which may be related to improved osmotic stress tolerance. Together, these findings demonstrate that ZmBET5L1 inhibits primary root growth and decreases osmotic stress tolerance by regulating vesicle transport and auxin distribution. This study has improved our understanding of the role of tethering factors in response to abiotic stresses and identified desirable variants for breeding osmotic stress tolerance in maize. Summary statement: ZmBET5L1 is a predicted tethering factor involved in vesicle trafficking to inhibit primary root growth and decrease osmotic stress tolerance in seedling roots, possibly by influencing auxin distribution in maize ( Zea mays L.).